Prevention, diagnosis, and management of Japanese encephalitis in children - Kumar R (Dove Medical Press, 2014)
Rashmi Kumar Department of Pediatrics, King George Medical University, Lucknow (UP), India Abstract: Japanese encephalitis is the single largest cause of viral encephalitis in the world today. It is caused by a Flavivirus whose natural cycle occurs in mosquito and vertebrate hosts (ardeid birds and pigs) and man is an incidental dead-end host. It tends to occur in outbreaks in poor rural regions of Asia where rice growing and pig rearing are a way of life. The illness has three stages – a prodromal stage with fever, headache, vomiting, and other nonspecific symptoms, an acute encephalitic stage with convulsions, coma, and signs of raised intracranial tension, and a convalescent stage. Differential diagnosis is very wide and even during epidemics it can be mimicked by many infectious and noninfectious disorders. The mainstay of laboratory diagnosis is the antibody capture enzyme-linked immunosorbent assay technique in cerebrospinal fluid. Treatment is essentially supportive and no antiviral has yet proven effective in randomized controlled trials. The mainstay of prevention is by vaccination. Many effective and safe vaccines are available and the IXIARO® vaccine – an inactivated vaccine from the SA-14-14-2 strain grown in vero cells – has received US Food and Drugs Administration approval. Japanese encephalitis control is thus a global health priority. Keywords: JE vaccine, occurrence, natural cycle, acute encephalitis syndrome